THE IMPORTANCE GIVEN TO THE DIFFERENT ASPECTS OF THE PHYSICAL SELF: A QUESTIONNAIRE - Goñi Grandmontagne, Alfredo; Ruiz de Azúa García, Sonia; Rodríguez, Arantzazu (Anales de Psicología / Annals of Psychology, 2005)
The CIDAF (Cuestionario sobre la Importancia de Distintos Aspectos Físicos/Questionnaire about the Importance of Different Physical Aspects) is an instrument designed to measure the perceived discrepancy between real and ideal physical self-concept in four aspects or dimensions of the physical self (physical ability, physical condition, body attractiveness and strength). As well as that, it also measures the degree of importance assigned to that discrepancy. A sample of 359 adolescents (183 males and 176 females) aged between 13 and 21 years were given the scale, which consists of 8 items. The exploratory factor analysis isolated two factors: discrepancy and importance, which explained 65% of the variance. The reliability of internal consistence of the test can be represented as follows: α = .82. Significant differences related to genre, age and sport practice were found in the subscales of CIDAF.